THE PROTECTION OF ARTISTIC WORK UNDER INDIAN COPYRIGHT LAW - Jilova, Nishant Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This research paper examines the legal framework for the protection of artistic works under the Indian Copyright Act, exploring the scope of copyright protection, the challenges faced by artists in enforcing their rights, and the impact of recent amendments and judicial interpretations on the safeguarding of artistic creations in the country. Under the Indian Copyright Act of 1957, which is the primary legislation governing copyright in the country, a wide array of works is eligible for copyright protection, encompassing not only literary and dramatic compositions, but also musical creations and artistic works. However, the application of copyright law to the field of art has been a subject of ongoing scholarly discourse, with concerns raised regarding the potential for content-based laws to have a chilling effect on the publication and dissemination of artistic works, as navigating the legal system should a work be impugned is invariably arduous, with the process itself often serving as a form of punishment, as Lawrence Liang once put it with reference to laws criminalising certain content which could be deemed socially or politically contentious. This paper will delve into the nuances of copyright protection for artistic works in India, examining the evolution of the legal framework, the challenges faced by artists, and the potential impact of recent legislative and judicial developments on the safeguarding of artistic expression in the country.